IN VIVO ANTIPLASMODIAL ACTIVITY OF METHANOL ROOT EXTRACT OF CISSUS CORNIFOLIA (BAKER) PLANCH - Maitama, Yusuf Adamu; Doma, Abdullahi Ibrahim; Aliyu, Musa (FUDMA JOURNAL OF SCIENCES, 2025)
The plant Cissus cornifolia belongs to the family vitacea. It is traditionally employed in the treatment of many ailments including malaria. The root was cold macerated using 70% methanol while phytochemical analysis was carried out to determine the secondary metabolites using standard protocol. The median lethal dose was then determined by exploiting the OECD protocol. The antiplasmodial activity was evaluated in mice intraperetonially infected with chloroquine sensitive plasmodium berghei-berghei using suppressive, prophylactic, and curative experimental models. Cissus cornifolia root extract revealed the presence of alkaloids, flavonoids, steroids/terpenoids, cardiac glycosides, carbohydrates, phenols, anthraquinones, and tannins. The oral LD50 of crude extract in mice was estimated to be greater than 5000 mg/kg per body weight. Curative effect of crude extract at doses of 250 mg/kg, 500 mg/kg and 1000 mg/kg showed statistical dose dependent significant reduction in mean parasitemia with a p value of 0.001. The standard drugs artesunate and chloroquine offered 85% and 90% respectively, when compared with non-treated mice. The extract, significantly prolonged mean survival time of mice infected with the parasites when compared with the distilled water administered group (Negative). Chemosuppresive effect showed reduction in mean parasitemia with suppression in the extract, chloroquine and artesunates administered groups as compared with the distilled water group. Prophylactic activity showed percentage parasite clearance of 62%, 73% and 65% with the different doses of the extract and 84% clearance for pyrimethamine when compared with negative group. The findings revealed that the extract possess antiplasmodial activity thereby validating its uses in folkloric medicine.
Keywords: Antiplasmodial; Cissus cornifolia; In vivo; Methanol; Plasmodium berghei